Regenerative management increases the efficacy of dung arthropod communities - Schmid, Ryan B.; Welch, Kelton D.; Lundgren, Jonathan G. (Frontiers in Sustainable Resource Management, 2025)
IntroductionRegenerative pasture management seeks to maintain ranchers' economic viability by maximizing grassland biodiversity and ecosystem functionality to maintain production and reduce input costs through improved ecosystem services. Dung arthropod communities contribute to two important ecosystem services for ranchers: dung degradation and pest control.MethodsWe examined the effect of regenerative pasture management on key beneficial dung-dwelling arthropods (coprophages, predators, and parasitoids) and measured dung fouling of pastures and pest abundance in dung pats (fly pests and parasites). Bioinventories of the adult dung-dwelling arthropod communities were collected from regeneratively (n = 18) and conventionally managed pastures (n = 21) extending from northeastern South Dakota to central North Dakota.ResultsIn total, 51,283 arthropod specimens were collected from 596 dung pats. Pats were also sampled for insect pests and cattle parasites: 20% of the pats contained adult fly pests, and 95% were infested with parasites. Regenerative pasture management did not increase the overall dung arthropod abundance or diversity, nor were there consistent effects on key beneficial arthropod groups throughout the grazing season. However, pasture fouling was significantly reduced in regeneratively managed pastures. Regenerative pastures also had low levels of insect pests, comparable to their conventional counterparts.DiscussionNotably, the majority (76%) of conventional ranchers used parasiticides/insecticides as part of their pest control program, while only 11% of regenerative ranchers utilized these inputs, opting instead for management to achieve similar results. This work demonstrates that regenerative grassland management aimed at grassland functionality can foster ecosystem services that contribute to ranchers' economic viability.